Credit Markets and Stagnation in an Endogenous Growth Model - De Gregorio, Jose (IMF Working Papers; Working Paper ;, 1993)
This paper studies the effects that the inability of individuals to borrow against future income has on economic growth. The model assumes that human capital, which is accumulated through education, is the only factor of production. It is shown that liquidity constraints reduce growth. Further, in the presence of externalities that may induce two equilibria, it is shown that liquidity constraints not only reduce the rate of growth in the high-growth equilibrium, but can also make the low-growth equilibrium more likely to occur.